Porównanie najlepszych praktyk w zakresie tworzenia efektywnych systemów gwarantowania depozytów bankowych - Janusz, Alicja (Comparison of best practices in the construction of efficient bank deposits guarantee systems, 2007)
Theoretical considerations and empirical experiences present the feasibility of designing guarantee systems in the way which enhances their most effective functioning. In order to support and disseminate the best patterns various units, so called best practices are created. The objective of the hereby study is to compare best practices in the domain of creating effective bank deposits guarantee systems, suggested by various world experts in this field. Authors of the analyzed recommendations, despite the application of different methods, have obtained very similar results related to many factors considered as the crucial components of a well designed protection system of bank deposits.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 76-87